Off-label use of bevacizumab in age-related macular degeneration: protocol for a systematic review and meta-analysis - Estarreja, João (2022)
Background: Age-related macular degeneration (AMD) is recognized as the leading cause of vision loss in elderly people. Taking into account the phenomenon of aging worldwide, the prevalence of AMD is expected to increase gradually in the future. AMD can be divided into early, intermediate and late stages, where early and intermediate are mainly asymptomatic, late-stage can be classified as non-vascular AMD and vascular AMD. Current pharmacological treatment in vascular AMD includes the administration of anti-VEGF agents, such as ranibizumab, pegaptanib, and aflibercept. Additionally, it has been reported that the off-label use of bevacizumab, through intravitreal administrations, demonstrates to be effective along with a lower cost in comparison to other agents used, which makes it a new possible pharmacological approach. Objective: This review aims to evaluate the efficacy, safety, and efficiency of the use of bevacizumab in the treatment of neovascular AMD. Methods: To identify and select relevant articles present in current literature, it will be developed a highly sensitive search strategy. To develop this search, it will be used MEDLINE via the Pubmed platform. It will be only considered randomized controlled clinical trials, where it is compared the use of bevacizumab with another pharmacological agent, such as ranibizumab, or even a placebo, in patients aged 50 years and older, diagnosed with vascular AMD. Results: This project has no funding and it has been done by a multidisciplinary research team of pharmacologists and orthoptists. The study was initiated in May 2021 with the lineation of the protocol, now the data are been extracted and analyzed, and it is expected to be released by the end of 2022. Conclusions: This review will provide a synthesis of the current information and underlying evidence, about the influence of the off-label use of bevacizumab in this disease. Altogether, it will allow having a clearer vision of a new possible accepted pharmacological approach for the treatment of vascular AMD. Clinical Trial: The protocol for this review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) with the code CRD42021244931.